(untitled) (Semiárida, 2020)
Swine production was incentivated and promoted through public policies, not only national ones but also provincial ones. Therefore this work’aim is to describe and identify those policies and evaluate their impact among 2010 -2014 in production. Besides these policies are divided according to the end they have. Relevant information about theem was obtained by means of interviews to important swine production producers, internet data from official pages related to the topic and bibliographic researches. A careful analysis of the period in which the production had a growth of 60,14% was also taken into consideration. In that time our province reached almost 149.476 porks. The biggest growth was in the north of our province mainly in Maracó department. It is important to highlight that many of the policies got better results than others. The bests ones were swine activation and cluster swine plan. These two ones were not alone, they could be framed among Agrifood and Agroindustry Strategic Plan and provincial Productive Development Plan. Directora: Melazzi, María Marta - Co Directora: Trotta, María Claudia